[Waterfall and River in Herðubreið Area] - Streng, Evelyn Fiedler (1975)
Photograph of a waterfall and river in the Herðubreið area. The white river cuts through a dark dirt field sparsely covered in green grass in the foreground. A small waterfall falls into the river to the left beside a stack of stones to its right. The square, dark volcano, Herðubreið, is visible in the distance, its snow capped peak sat on its left side. Clouds cover the white sky above the ground where a person stands along the river to the left.